2012
DOI: 10.1089/end.2011.0340
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Institutional Analysis of Robot-Assisted Partial Nephrectomy for Renal Tumors >4 cm Versus ≤4 cm in 445 Consecutive Patients

Abstract: Background and Purpose: Robot-assisted partial nephrectomy (RPN) has emerged as a viable approach to minimally invasive surgery for small renal tumors. There are few reports of RPN for tumors > 4 cm. Our objective was to evaluate outcomes of RPN for tumors > 4 cm compared with RPN for tumors £ 4 cm in a large multi-institutional study. Patients and Methods: We reviewed data for 445 consecutive patients who underwent RPN by experienced surgeons at four academic institutions from 2006 to 2010. Patients were stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 21 publications
7
45
0
Order By: Relevance
“…The first report on the single-surgeon, single-center experience of RAPN for renal tumors was published from VUI, comparing T1a with larger tumors, and found equivalent EBL, total operative time, LOS, complication rates and change in estimated glomerular filtration rate (eGFR) in the two groups [54]. Multiinstitutional series later confirmed our results even for more complex tumors [55] and in obese patients [56].…”
Section: Robotic Upper Tract and Renal Surgerysupporting
confidence: 75%
See 1 more Smart Citation
“…The first report on the single-surgeon, single-center experience of RAPN for renal tumors was published from VUI, comparing T1a with larger tumors, and found equivalent EBL, total operative time, LOS, complication rates and change in estimated glomerular filtration rate (eGFR) in the two groups [54]. Multiinstitutional series later confirmed our results even for more complex tumors [55] and in obese patients [56].…”
Section: Robotic Upper Tract and Renal Surgerysupporting
confidence: 75%
“…Although long-term success rates could not be bettered, Hemal et al [62] reported better quality of suturing and faster perioperative parameters of dissection time, intracorporeal suturing, and overall operating time using robotic interface when compared to conventional pyeloplasty. Sukumar and colleagues [63] found that use of minimally invasive pyeloplasty increased dramatically from 2.4% to 55 Pelvic organ prolapse (POP) affects 30% of women aged above 50 years, and needs surgical repair in 11% by 80 years. Robotic sacrocolpopexy (RSC) became a natural successor to its laparoscopic counterpart, as the procedure was being performed in a limited pelvic space with need for intracorporeal suturing.…”
Section: Reconstructive Proceduresmentioning
confidence: 99%
“…28,29 Mean warm ischemia time is routinely reported as less than 30 minutes even for larger and more complex tumors. 26,30 Thus, the ability of a nephrometry scoring system to potentially predict ischemia time may have limited clinical significance with respect to the anticipated eGFR decrease resulting from NSS, as supported by the findings of Hayn et al 23 Our cohort was heterogeneous with respect to the application of renal ischemia (none vs warm vs cold) and most procedures were done under warm ischemia. Since no ischemia and cold ischemia techniques are renal protective 8 -10 and might have less impact on eGFR after PN than warm ischemia techniques, there might have been a greater impact on eGFR in our study cohort using this ischemia technique.…”
Section: Discussionmentioning
confidence: 78%
“…15,19,20 As expected, this score was significantly correlated with the WIT, operative time, estimated blood loss and complication rate. 21 Surgery for a deep endophytic hilar mass will be more technically challenging than that for an exophytic lower pole T1a tumour. Our study population included a significant proportion of moderately to highly complex tumours (69.4%) and of tumour >7 cm (7.7%).…”
Section: Discussionmentioning
confidence: 99%